Collagen Partition in Polymeric Aqueous Two-Phase Systems for Tissue Engineering - Singh, Sunil; Tavana, Hossein (Frontiers in Chemistry, 2018)
Aqueous two-phase systems (ATPS) of polyethylene glycol (PEG) and dextran (DEX) are commonly used to partition proteins. Protein partition in ATPS is a complex phenomenon and depends on factors including molecular weight of polymers, and electrochemical and ionic properties of the phases. We studied the effect of polymer molecular weight on the partition of a natural protein, collagen, in several ATPS formulations made with non-ionic polymers polyethylene glycol (PEG) and dextran (DEX). We found that partitioning of collagen to an aqueous phase significantly increases when the molecular weight of the corresponding phase polymer decreases. Additionally, a large difference between the molecular weight of the phase-forming polymers was necessary to cause a significant uneven collagen distribution between the aqueous phases. We then employed one of the system to create a three-dimensional breast cancer microtissue by entrapping a spheroid of breast cancer cells within the partitioned collagen. This convenient technique to generate 3D microtissues offers a convenient and promising approach for tissue engineering applications.